V.v. Barthold’s Contribution to Oriental Studies in Tsarist Russia - Babayeva, Nigar (Scholarya Demo Journal of Ruby, 2019)
Vasily Vladimirovich (Wilhelm) Barthold, a Russian historian of German descent, was one of the most important figures in Oriental Studies in Russia who devoted his entire life to the study of the history of Central Asia and Turkestan. While playing an important role in the institutionalization of Oriental Studies in Russia by producing hundreds of works in this field, he also tried to understand and examine the foundations of Oriental Studies in the West. Giving importance to new resources, the essential part of Barthold’s research methodology was to strive to gather and publish all the available resources together. He dedicated his whole life to this work and made it his duty to find all available resources in order to publish them. The fact that he dealt with scientific facts without being under ideological influence was accepted as one of the most important features that distinguished him from other Orientalists before and after him and he was regarded as the authoritative personality in Central Asian history in the West. Barthold’s studies on the history of the Turkic and Mongol peoples are divided into two periods: 1892-1899 and 1925-1930. He produced valuable works on Turkology, Iranology and Islam, and in his research he drew attention to the history of religions that spread in Central Asia and Iran such as Zoroastrianism, Buddhism, Christianity and especially Islam. From 1963 to 1977 all his works were published in ten volumes in Moscow. These works, the majority of which have been translated into Turkish, have not been studied in detail until now, and readers were generally provided with biographical information about Barthold and bibliographical lists of his works. The aim of this study is to present Barthold’s views on Turkic peoples and Islam, to touch upon the prevailing conception of Muslim Turkic peoples in Russia during his lifetime and to give information about Oriental Studies in general and Turkology in particular.